Single-Step Renal Dilatation Is a Novel Technique in Percutaneous Nephrolithotomy: A Prospective Randomised Study (Bangladesh Journal of Urology, 2020)
Purpose: To evaluate the feasibility, safety and efficacy of one-shot dilation (OSD) in percutaneous nephrolithotomy (PCNL).Materials and Methods: In a prospective randomised study including 62 patients divided into two groups, the first had RD before PCNL using the standard metallic telescopic dilators (Alken), and the second had RD using the 30-F Amplatz dilator over the central Alken dilator. The operative duration, with X-ray exposure, was calculated. The procedure outcome in terms of complications, stone-free rates and hospital stay was evaluated statistically.Results : The tract was dilated correctly in all cases. The operative duration and X-ray exposure was shorter in patients undergoing single-step RD (P < 0.05). There were perioperative complications, according to the Clavien grading system, in 15 (25%) patients but there was no statistically significant difference between the groups. The stone-free rates were comparable in both groups.Conclusion : A single-step RD during PCNL is feasible, with a shorter operative duration and X-ray exposure. The outcomes were comparable with those of a standard metallic telescopic RDBangladesh Journal of Urology, Vol. 20, No. 2, July 2017 p.70-73